INFLUENCE OF INCORPORATED LABLAB PLANTED AT VARIOUS SPACINGS ON PRODUCTIVITY OF MAIZE (ZEA MAYS L.) VARIETIES IN NORTHERN GUINEA SAVANNA ZONE OF NIGERIA - Adesoji, Aderemi; Oyebamiji, Noah; Abubakar, Ibrahim (FUDMA JOURNAL OF SCIENCES, 2020)
The study was conducted to evaluate the effect of incorporated lablab planted at various spacings on productivity of two maize (Zea mays L.) varieties in northern Guinea Savanna zone of Nigeria. Field experiment was carried out at the Research Farm of the Institute for Agricultural Research, Ahmadu Bello University, Zaria, Nigeria. The treatments consisted of two varieties of maize (SAMMAZ 28 and SAMMAZ 29) and six green manure lablab (Lablab purpureus) plant spacings viz. 25cm x 10cm, 25cm x 20cm, 25cm x 30cm, 50cm x 10cm, 50cm x 20cm and 50cm x 30cm. The experiment was laid out in a Randomized Complete Block Design (RCBD) in factorial arrangement and was replicated three times. SAMMAZ 29 performed significantly (P<0.05) better than SAMMAZ 28 on growth, yield components and grain yield (kg ha-1) of maize. Incorporation of lablab planted at various spacing significantly increased grain yield (kg ha-1) and all the maize parameters studied except cob diameter. In combined mean, incorporation of lablab planted at 25cm x 30cm significantly increased grain yield but at par with incorporation of lablab planted at spacing 50cm x 30cm. In combined mean, incorporation of lablab planted at 25cm x 30cm gave 18.2, 20.5, 18, 28.6 and 13.6% better grain yield than incorporation of lablab planted at spacings 25cm x 10cm, 25cm x 20cm, 50cm x10cm, 50cm x 20cm and 50cm x 30cm, respectively. Conclusively, incorporation of lablab planted at 25cm x 30cm was better than other spacings on SAMMAZ 29.